GIS: The key to success in submarine pipeline routing - Mahmud, Razali (2006)
Various tools and techniques are used to ensure the maximum safety of the submarine pipelines. However, the resulting consequence of these tools and techniques is the ever increasing data volumes, with the management and subsequent analysis of the data becoming more and more of an issue. The objective of this paper is to elaborate the implementation of GIS technology for submarine pipeline routing design evaluation. With GIS, various routing criteria could be taken into consideration to identify the Least Cost Path (LCP) of the pipeline analytically, precisely and efficiently. Examples of these criteria are vessel anchoring, discarded objects left on the seabed, seabed irregularities, wave characteristics, subsurface current & pressure, hydrodynamic forces and soil stability.